PENGARUH PLATFORM E-COMMERCE DAN FAKTOR INTERNAL PADA KEBERLANGSUNGAN USAH MIKRO, KECIL, DAN MENENGAH (UMKM) KERIPIK DI KABUPATEN MALANG - Rifki As'ad, Achmad; Muhammad Dandy Alif Wildana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
One of the regions in East Java that shows significant potential in the development of Micro, Small and Medium Enterprises (MSMEs) is Malang Regency. Malang Regency, which is the second largest district, has great potential in having many MSMEs compared to other districts or large cities. This research aims to determine the amount of income of Micro, Small and Medium Enterprises (MSMEs). Variables include Capital (X1), Labor (X2), Length of Business (X3), E-Commerce (X4). Primary data for this study was gathered through unstructured interviews, with a sample size of 70. The data analysis method used in this research was multiple linear regression which was used to test the income model. The results of this research show that capital and length of business have a positive and significant effect on the income of MSME chips in Malang Regency, while the variables of e-commerce and labor have no effect on MSME income. The independent variables together influence the income of Chips MSMEs in Malang Regency by 50.3 percent.